Cell-specific Retention and Action of Pheophorbide-based Photosensitizers in Human Lung Cancer Cells - Tracy, Erin C. (Photochem Photobiol, 2018)
This study determined in primary cultures of human lung cancer cells the cell specificity of chlorin-based photosensitizers. Epithelial cells (EC) preferentially retained 3-[1-hexyloxyethyl]-2-devinylpyropheophorbide-a (HPPH) and related structural variants. Tumor-associated fibroblasts (Fb) differ from EC by a higher efflux rate of HPPH. Immunoblot analyses indicated dimerization of STAT3 as a reliable biomarker of the photoreaction. Compared to mitochondria/ER-localized photoreaction by HPPH, the photoreaction by lysosomally targeted HPPH-lactose showed a trend toward lower STAT3 crosslinking. Lethal consequence of the photoreaction differed between EC and Fb with the latter cells being more resistant. A survey of lung tumor cases indicated a large quantitative range by which EC retain HPPH. The specificity of HPPH retention defined in vitro could be confirmed in vivo in selected cases grown as xenografts. HPPH retention as a function of the tetrapyrrole structure was evaluated by altering side groups on the porphyrin macrocycle. Presence or absence of a carboxylic acid at position 17(2) proved to be critical. A benzyl group at position 20 enhanced retention in a subset of cancer cells with low HPPH binding. This study indicated experimental tools that are potentially effective in defining the photosensitizer preference and application for individual patient’s cancer lesions.